Contemporary figures of social absence - Iñaki Robles Elong (Oñati Socio-Legal Series)
This article reflects on the scope of the concept of absence to think about social disappearance. It is based on the definition of absence as the breaking of the social bond that unites a subject with the political community and dwells within the limits of citizenship and the human. Some sociological traditions were sensitive to enumerate different characters of social absence by their condition of disaffiliated, unprotected and destitute of the elements that constitute the subject in the epicenter of social life, citizenship. They are invisible, they are out of order. This article seeks a reflection and another approach to thinking about social absence through some of its contemporary characters that "shine by its absence". In this way, contribute to the debate and enrich the understanding of the social disappearance.